2012
DOI: 10.1161/circoutcomes.112.967638
|View full text |Cite
|
Sign up to set email alerts
|

Most Important Articles on Cardiovascular Disease Among Racial and Ethnic Minorities

Abstract: The following are highlights from the new series, Circulation: Cardiovascular Quality and Outcomes Topic Review. This series will summarize the most important manuscripts, as selected by the Editor, that have published in the Circulation portfolio. The objective of this new series is to provide our readership with a timely, comprehensive selection of important papers that are relevant to the quality and outcomes, and general cardiology audience. The studies included in this article represent the most significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

3
32
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 38 publications
(35 citation statements)
references
References 55 publications
3
32
0
Order By: Relevance
“…Moreover, because women and racial and ethnic minorities are underrepresented in published studies, the predictive value of D‐PA–based risk models for these patient groups is unknown. This is concerning, because traditional cardiovascular risk assessment tools have been shown to underestimate risk in women and minority patients …”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, because women and racial and ethnic minorities are underrepresented in published studies, the predictive value of D‐PA–based risk models for these patient groups is unknown. This is concerning, because traditional cardiovascular risk assessment tools have been shown to underestimate risk in women and minority patients …”
Section: Resultsmentioning
confidence: 99%
“…This is concerning, because traditional cardiovascular risk assessment tools have been shown to underestimate risk in women and minority patients. 39,40…”
Section: D-pa In Risk Stratification Modelsmentioning
confidence: 99%
“…Additionally, entrenched institutional racism leads to inequities in access to and quality of health care. Studies have demonstrated pervasive disparities between treatment of blacks and whites in health care delivery in realms such as clinician adherence to prescribing guidelines, therapy intensification, and use of invasive cardiac procedures, even after controlling for clinical and socioeconomic factors [1].…”
Section: Race Influence On Access and Quality Of Carementioning
confidence: 99%
“…
It is now well documented that there are profound race-associated disparities among those who are affected by and die from cardiovascular disease (CVD) [1]. These disparities are deeply rooted within the history of race and medicine in the US.
…”
mentioning
confidence: 99%
“…The quality of cardiovascular care for racial and ethnic minorities is known to vary (9). The rate of preventable hospitalizations for conditions that include HF is highest for black and Hispanic subjects compared with white subjects (10).…”
mentioning
confidence: 99%